2013
DOI: 10.26522/brocked.v23i1.353
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers' Self-Regulated Learning and their Developing Concepts of SRL

Abstract: Self-regulated learners manage their thoughts, emotions, and behaviours, and their social and contextual environments to reach their learning goals. Research shows that student teachers can learn to teach in ways that promote students’ development of SRL. It has also been shown that there is a relationship between teachers’ own SRL and their ability to develop self-regulation in students. This study examined student teachers’ developing concepts of SRL as they learned about this complex set of skills, behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
0
25
0
5
Order By: Relevance
“…Hashemyolia et al, 2014; Turan and Konan, 2012; Vrugt and Ourt, 2008). For instance, Buzza and Allinotte (2013) reported that Canadian teacher candidates majoring in education scored 4.82 on average on SRL strategies scales. Turan and Konan (2012) surveyed a group of fourth-year Turkish undergraduate students during their surgery internship.…”
Section: Discussionmentioning
confidence: 99%
“…Hashemyolia et al, 2014; Turan and Konan, 2012; Vrugt and Ourt, 2008). For instance, Buzza and Allinotte (2013) reported that Canadian teacher candidates majoring in education scored 4.82 on average on SRL strategies scales. Turan and Konan (2012) surveyed a group of fourth-year Turkish undergraduate students during their surgery internship.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers' SRL knowledge and skills allow them to promote their students' own SRL by externally regulating their cognition, behaviours, and motivation. This reciprocal relationship has been found to be critical to student learning (Buzza & Allinotte, ; Michalsky & Schechter, ; Peeters et al, ; Perry, Hutchinson, & Thauberger, ; Perry, Phillips, & Dowler, ; Perry, Phillips, & Hutchinson, ; Randi, ; Randi & Corno, ; Wolters & Pintrich, ). There is, therefore, a need for student teachers to receive training in SRL, not only for themselves as learners but also as teachers to support their students (Moos & Ringdal, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…mit der Vermittlung von optimalen Zielorientierungen zusammenhängen. Verschiedene Studien zeigen jedoch, dass SRL-Strategien bislang auch an Schulen nur selten vermittelt werden (Buzza & Allinotte 2013). Dies liegt nicht unbedingt daran, dass den Lehrkräften die Motivation dazu fehlt -ganz im Gegenteil.…”
Section: Relevanz Des Selbstregulierten Lernens Für (Angehende) Lehrkunclassified